2013
DOI: 10.1007/s12011-013-9732-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring with Honeybees of Heavy Metals and Pesticides in Nature Reserves of the Marche Region (Italy)

Abstract: The aim of this study was to carry out biomonitoring with honeybees (Apis mellifera L.) to assess the presence of pesticides and heavy metals (cadmium, chromium, nickel, lead) in all of the ten nature reserves of the Marche Region (central–eastern Italy). The study was carried out during the spring and summer seasons when the honeybees were active, over 3 years (2008–2010). Twenty-two colonies of honeybees bred in hives were used. Samples of live and dead honeybees and of honey were collected from 11 sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 26 publications
3
41
1
2
Order By: Relevance
“…Metal concentrations found in honey samples in this study are lower than residual levels obtained by other author in honey from Turkey (Erbilir & Erdogrul, 2005) and Spain (Frias et al, 2008), similar to that obtained in other region of Italy (Ruschioni et al, 2013;Perna, Simonetti, Intaglietta, Sofo, & Gambacorta, 2012) but higher than in France (Lambert et al, 2012). Considering the different floral types, the comparative analysis of metals residual levels in our honey samples (Figure 1) showed higher levels of both Pb and Cd in chestnut honey vs eucalyptus (in accordance with Perna et al, 2012) and vs carob samples.…”
Section: Discussionsupporting
confidence: 89%
“…Metal concentrations found in honey samples in this study are lower than residual levels obtained by other author in honey from Turkey (Erbilir & Erdogrul, 2005) and Spain (Frias et al, 2008), similar to that obtained in other region of Italy (Ruschioni et al, 2013;Perna, Simonetti, Intaglietta, Sofo, & Gambacorta, 2012) but higher than in France (Lambert et al, 2012). Considering the different floral types, the comparative analysis of metals residual levels in our honey samples (Figure 1) showed higher levels of both Pb and Cd in chestnut honey vs eucalyptus (in accordance with Perna et al, 2012) and vs carob samples.…”
Section: Discussionsupporting
confidence: 89%
“…Overall in honey, no low concentrations of heavy metals were detected w hich showed no relationship to the concentrations detected in live honeybees. The results show that live honeybees are the preferred matrix for the detection of heavy metals over dead bees and honey (Ruschioni et al, 2013). Satta et al (2012) conducted a three-year biomonitoring study in Italy, using honeybees, honey and pollen and ants to detect heavy metals (Cd, Cr and Pb) in a post mining area in Sardinia.…”
Section: State Of the Art Bio-indication With Honeybee Coloniesmentioning
confidence: 99%
“…The incidence of pesticides and heavy metals over a three-year study (2008)(2009)(2010) in natural reserves in the Marche region in Italy has been studied in live bees, dead bees and honey. Pesticides have not been detected (Ruschioni et al, 2013). In the United States a broad survey study of pesticides residues in wax, pollen and bees revealed high levels of multiple pesticides in bee collected pollen.…”
Section: Pesticides Honeybeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Estes contaminantes frequentemente se incorporam no tecido das abelhas, pólen, cera, mel ou na própria colméia (WALLWORK-BARBER et al, 1982;BROMENSHENK et al, 1985). Abelhas tem sido usadas como monitoras da presença e distribuição de elementos químicos, incluindo fluoretos (BROMENSHENK et al, 1988;MAYER et al, 1988), arsênio (TERZIC et al, 1984), chumbo (BARISIC et al, 1999), zinco (ASSMANN-WERTHMÜLLER, 1991) níquel (RUSCHIONI et al, 2013), cádmio (RUSCHIONI et al, 2013), potássio (BARBATINI et al, 1991), e a biodisponibilidade de radionuclídeos, incluindo césio, trítio, estrôncio e plutônio (HAKONSON;BOSTICK, 1974;FRESQUEZ, 1997). A integração das análises de radionuclídeos e/ou elementos químicos em abelhas com as de seus recursos alimentares, pólen e mel, fornecem uma informação mais detalhada sobre a dinâmica destas substâncias ambiente (PORRINI et al, 2002).…”
unclassified